Can Classifications Adequately Represent Genital Malformations? - Kiblboeck, Stephanie; Oppelt, Peter; Oppelt, Patricia; Stein, Raimund; Ommer, Stefanie; Pavlik, Roman; Rall, Katharina; Kongrtay, Kuralay; Wagner, Helga; Hermann, Philipp; Trautner, Philip Sebastian (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Genital malformations are a common clinical occurrence that can be represented using different classifications. Reproducibility is an essential quality characteristic for a classification, and it plays an important role, especially in consultations and the treatment of infertile patients and in obstetric management. The aim of this study is to demonstrate the reproducibility and clinical practicality of three commonly used classifications: the ESHRE/ESGE (European Society of Human Reproduction and Embryology/ European Society for Gynecological Endoscopy), VCUAM (Vagina Cervix Uterus Adnex-associated Malformation), and AFS (American Fertility Society) classifications.Materials and Methods Sixty-five patients with female genital malformations were included in this prospective, multicenter, exploratory, observational study. All participants underwent a clinical examination and a medical interview. The investigators were instructed to classify the presenting malformations according to the ESHRE/ESGE, VCUAM, and AFS classifications using a structured questionnaire. Investigators were asked whether the malformation could be reproducibly classified (yes/no) and about the grade (grade 1–5 from “very good” to “deficient”) they would assign to each classification. Classification assessment was queried for vagina, cervix, uterus, adnexa, and associated malformations and was scored from 1 to 5.Results Reproducibility was rated as 80% (n = 52/65), 92.3% (n = 60/65), and 56.9% (n = 37/65) for the ESHRE/ESGE, VCUAM, and AFS classification, respectively. ESHRE/ESGE, VCUAM and AFS were rated as “very good” or “good” for 83.3%, 89.2%, and 10.8% of vaginal malformations; for 75.8%, 87.5%, and 24.2% of cervical malformations; and for 89.7%, 89.5%, and 86.2% of uterine malformations, respectively. VCUAM was rated as “very good” or “good” for 77.8% and 69.6% of adnexal malformations and associated malformations, respectively. ESHRE/ESGE and AFS were rated as “sufficient” or "deficient” for 100% and 75% of adnexal malformations and for 77.3% and 69.6% of associated malformations, respectively.Conclusion The prospective multicenter EVA (ESHRE/ESGE | VCUAM | AFS) study revealed that the organ-based ESHRE/ESGE and VCUAM classifications of female genital malformations perform better in terms of reproducibility as well as in the assessment of individual compartments than the non-organ-based AFS classification.
Keywords: EVA-Studie; weibliche genitale Fehlbildungen; Gebärmutterfehlbildung; genitale Klassifikation